Addition of P-H Bonds to Heterocumulenes - Huke, C. D. (2023)
In the pursuit of synthesising novel heteroatom-rich phosphorus analogues of ubiquitous ureas, thioureas and guanidines in a sustainable manner, an atom efficient hydrofunctionalisation approach was undertaken. Either by catalysis or catalyst-free (where viable), testing the addition of different P-H bond containing substrates to multiple bond containing heterocumulenes; isocyanates (RN=C=O), isothiocyanates (RN=C=S) and carbodiimides (RN=C=NR).